Auxin production as an integrator of environmental cues for developmental growth regulation - Mroue, Souad; Simeunovic, Andrea; Robert, Hélène S (Journal of experimental botany, 2018)
Being sessile organisms, plants have evolved mechanisms allowing them to control their growth and development in response to environmental changes. This occurs by means of complex interacting signalling networks that integrate diverse environmental cues into co-ordinated and highly regulated responses. Auxin is an essential phytohormone that functions as a signalling molecule, driving both growth and developmental processes. It is involved in numerous biological processes ranging from control of cell expansion and cell division to tissue specification, embryogenesis, and organ development. All these processes require the formation of auxin gradients established and maintained through the combined processes of biosynthesis, metabolism, and inter- and intracellular directional transport. Environmental conditions can profoundly affect the plant developmental programme, and the co-ordinated shoot and root growth ought to be fine-tuned to environmental challenges such as temperature, light, and nutrient and water content. The key role of auxin as an integrator of environmental signals has become clear in recent years, and emerging evidence implicates auxin biosynthesis as an essential component of the overall mechanisms of plants tolerance to stress. In this review, we provide an account of auxin's role as an integrator of environmental signals and, in particular, we highlight the effect of these signals on the control of auxin production.
Keywords: signální transdukce; temperature; Plant Development; kyseliny indoloctové; Indoleacetic Acids; Signal Transduction; vývoj rostlin; regulátory růstu rostlin; heavy metal; nutrients; auxin; salinity; plant development; shade avoidance; Abiotic stress; Environment; Plant Growth Regulators; životní prostředí; drought